Complex Morphogenesis by a Model Intrinsically Disordered Protein. Issue 51 (20th November 2020) - González‐Obeso, Constancio; González‐Pérez, Miguel; Mano, João F.; Alonso, Matilde; Rodríguez‐Cabello, José Carlos
Abstract: The development of intricate and complex self‐assembling structures in the micrometer range, such as biomorphs, is a major challenge in materials science. Although complex structures can be obtained from self‐assembling materials as they segregate from solution, their size is usually in the nanometer range or requires accessory techniques. Previous studies with intrinsically disordered proteins (IDPs) have shown that the active interplay of different molecular interactions provides access to new and more complex nanostructures. As such, it is hypothesized that enriching the variety of intra‐ and intermolecular interactions in a model IDP will widen the landscape of sophisticated intermediate structures that can be accessed. In this study, a model silk‐elastin‐like recombinamer capable of interacting via three non‐covalent interactions, namely hydrophobic, ion‐pairing, and H‐bonding is built. This model material is shown to self‐assemble into complex stable micrometer‐sized biomorphs. Variation of the block composition, pH, and temperature demonstrates the necessary interplay of all three interactions for the formation of such complex structures. Abstract : Non‐covalent forces modulate the phase transition of naturally occurring self‐assembled structures. By varying the block composition, pH, and temperature, it demonstrated the necessary synergetic combination of three non‐covalent interactions present in an intrinsically disordered silk‐elastin‐like recombinamer for self‐assembly into micrometer‐sized complex biomorphs.